Association of Inflammatory Burden Index (IBI) with Clinical Outcomes in Acute Exacerbated COPD (Chronic Obstructive Pulmonary Disease) Patients with Respiratory Failure: Hospital based observational study - P V, Varshni; L, Muthukumaran; R, Sridhar; N, Meenakshi (Journal of Neonatal Surgery, 2025)
Background Acute exacerbations of Chronic Obstructive Pulmonary Disease (AECOPD) accelerate disease progression and increase healthcare burden. Systemic inflammation is a key contributor, yet comprehensive inflammatory markers for predicting ventilatory support needs remain underexplored. The Inflammatory Burden Index (IBI), integrating C-reactive protein (CRP), and neutrophil-to-lymphocyte ratio (NLR), may serve as a novel prognostic tool for non-invasive ventilation (NIV) dependency Materials and methods This observational cross-sectional study was conducted in a tertiary care hospital over six months, enrolling 64 AECOPD patients requiring hospitalization. IBI was calculated using CRP, neutrophil, and lymphocyte counts, and its association with NIV requirement at discharge was assessed. Data were analyzed using Mann-Whitney U test, Spearman’s correlation, and receiver operating characteristic (ROC) curve analysis to evaluate the predictive accuracy of IBI compared to other biomarkers. Results Patients with elevated IBI levels (79.4 ± 26 vs. 22.6 ± 27.1, p<0.001) were more likely to require NIV at discharge. IBI showed a strong positive correlation with pCO₂ (r=0.696, p<0.001) and a negative correlation with FEV1 (r=-0.465, p<0.001). ROC analysis demonstrated IBI’s superior predictive ability (AUC = 0.89, p<0.001) compared to NLR and CRP. Conclusion IBI is a strong predictor of NIV dependency and may aid in early risk stratification and treatment planning. Further multi-center validation is warranted to confirm its clinical utility.